Kontrak Kerja dan Kesejahteraan ABK Nelayan Perspektif Etika Bisnis Islam di Sarangmeduro, Jawa Tengah - Ani Fatmawati; Ana Toni Roby Candra Yudha; Hammis Syafaq (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
Analysis of work contracts on the welfare of crew in fishermen sector from the Perspective of Islamic business ethics in Sarangmeduro Village is a study that aimed to answer questions about how the fishermen sector work contracts are implemented and how the welfare of the crew members is applied in Sarangmeduro Village. The methodology used was descriptive qualitative method with the type of case study research on the object. The result of this research is that the work contract conducted by fishermen in Sarangmeduro Village is a work contract system that has been implemented from generation to generation and is more likely to approach the muzaroah contract in profit sharing of maro or paroan. Based on the field of employment, the fishermen in Sarangmeduro Village live in prosperity. By the opening jobs provided by ship employers, they are facilitated in finding work. The residence that is inhabited every year has changed, which was originally made of woven bamboo, now most of them are built of bricks. The existence of a work contract implemented by fishermen can help to boost the economic condition of the fishermen in Sarangmeduro Village, which is always developing. The researcher recommend that fishermen make work inovation.